MONITORING DAN EVALUASI CARA DISTRIBUSI ALAT KESEHATAN YANG BAIK (CDAKB) PADA PEDAGANG ALAT KESEHATAN PT.X DI KOTA BATAM - Yan Yan; Mona Asiah; Ovalina Sylvia Br. Ginting (Universitas Haji Sumatera Utara, 2022)
Distribution is an important aspect in ensuring the quality of the preparation. Medical Device Distributors must have adequate facilities and infrastructure to ensure the implementation of distribution, management, procurement, and storage. The purpose of this study was to determine Medical Device Distributors compliance with CDAKB requirements in the distribution of medical devices. This study uses the direct observation method on the research object to see the activities carried out and compare them with the CDAKB requirements listed in the Draft Technical Instructions for Supervision of Medical Device Distribution Facilities. Monitoring objects are documents, officers, facilities/infrastructure, and distribution activities. The results of the observations are the percentage of the level of fulfillment of the CDAKB requirements by dividing the total score achieved by the maximum number of scores and then multiplying by 100%. The results of the analysis of the level of CDAKB compliance show that PT. X meets 59 of 84 points (70.24%) requirements divided into 4 aspects, namely quality management system, resource management, product storage, and handling, and corrective actions, returns, and product destruction. In conclusion PT. X meets the CDAKB requirements and is in a good category.